Weakly Nonlinear Convection of a Maxwell Fluid in a Porous Layer With Coriolis Effect - Bheemudu, C.; Goud, T. Ramakrishna; Reddy, M. Pavan Kumar; Raghavendra, P. (Communications in Mathematics and Applications, 2023)
The linear and non-linear instability theories of a Maxwell fluid in a Darcy-Benard setup with coriolis effect is studied. For linear theory, the method of normal modes has been employed to solve governing dimensionless equations which led an eigenvalue problem and it is solved analytically. We obtained the expressions for steady and oscillatory thermal Rayleigh numbers. The effects of different physical parameters on steady and oscillatory convective phenomena are presented and described. In order to study the heat transport by convection the well-known equation, Landau-Ginzburg equation has been derived.